PENGALAMAN TENAGA KERJA INDONESIA ILEGAL DI MALAYSIA: Sebuah Penelitian Fenomenologis - Simanullang, Gonti; Bangun, Anselmus Chartino Ade; Utama, Ignatius L.Madya (UNIKA Santo Thomas, 2023)
The limited domestic job vacancies have caused many Indonesian citizens or Indonesian Migrant Workers (TKI) to seek work abroad. This certainly makes someone who is being squeezed by life's problems, especially economic problems, will eventually take all kinds of ways that are believed to be able to overcome their life problems. This is where illegal migration practices emerge, there are people who do not have complete documents, but want to work in Malaysia to make ends meet. This is further supported by the difficulty of obtaining work permits at the immigration office. However, being an illegal migrant worker does not make things easier. It turns out that there are many difficulties and risks that must be faced, even to the point of being life threatening. Using Moustakas' phenomenological research method, researchers try to explore the meaning of the experience of illegal migrant workers. Illegal status, which is very vulnerable to various risks, is felt to describe the whole experience more. Various difficulties while working as illegal migrant workers even with a large salary do not make them enjoy life. Finally they realize that a quiet, comfortable and safe life is much more valuable than just a big salary. The results of the phenomenological analysis at the synthesis stage in intuitive integration reveal the true meaning of this experience, namely a sense of peace is more valuable than a large salary. ini dibagi dua, yaitu usia perkawinan 0-5 tahun sebanyak 2 keluarga dan usia perkawinan 6-10 tahun sebanyak 2 keluarga.